1986
DOI: 10.1016/0378-4363(86)90021-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phase separation: Cluster kinetics and self-similarity property of the structure function

Abstract: We derive simple relations between the structure function, grain distribution and system excess energy during the phase separation processes occurring in a variety of mixtures suddenly cooled inside the miscibility gap. This allows to relate experimental observations performed by different techniques, namely small-angle scattering, microscopy and calorimetry, over a wide range of times and concentrations including the occurrence of percolation. We discuss in particular the self-similarity or dynamical scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In addition, for a lattice model it is no problem to define 'clusters' of reversed spins in terms of closed contours separating them from the surrounding up spins. Consequently the study of such clusters in the Ising model both for d = 2 and d = 3 has had much attention (Fisher 1967, Stoll et a1 1972, Muller-Krumbhaar 1974a,b, Muller-Krumbhaar and Stoll 1976, Binder 1976, Coniglio and Klein 1980, Binder et a1 1975, Stauffer et a1 1982, Dickman and Schieve 1982, Marro and Toral 1983, Jacucci et a1 1983, Hu 1984, Heermann et a1 1984, Binder and Heermann 1985, Heermann and Klein 1983a,b, Nauenberg and Cambier 1986. Despite this large activity, clusters in the Ising model are still incompletely understood, and hence our discussion will focus on a few aspects of this problem only.…”
Section: A F ( P ) = H ( 4 Y " " -4 F " " " ) P D V D + S D P D -' L N Tmentioning
confidence: 99%
“…In addition, for a lattice model it is no problem to define 'clusters' of reversed spins in terms of closed contours separating them from the surrounding up spins. Consequently the study of such clusters in the Ising model both for d = 2 and d = 3 has had much attention (Fisher 1967, Stoll et a1 1972, Muller-Krumbhaar 1974a,b, Muller-Krumbhaar and Stoll 1976, Binder 1976, Coniglio and Klein 1980, Binder et a1 1975, Stauffer et a1 1982, Dickman and Schieve 1982, Marro and Toral 1983, Jacucci et a1 1983, Hu 1984, Heermann et a1 1984, Binder and Heermann 1985, Heermann and Klein 1983a,b, Nauenberg and Cambier 1986. Despite this large activity, clusters in the Ising model are still incompletely understood, and hence our discussion will focus on a few aspects of this problem only.…”
Section: A F ( P ) = H ( 4 Y " " -4 F " " " ) P D V D + S D P D -' L N Tmentioning
confidence: 99%
“…Different theories lead to different expressions for C , ( t ) and C,, and recent Monte Carlo work has been carried out to distinguish between the different theoretical approaches, both for the dynamical properties (Penrose et a1 1978, Marro and Toral 1986, Toral and Marro 1987 and the equilibrium properties (Jan er al 1982, Marro and Toral 1983, Cambier and Nauenberg 1986. Series expansions have also been used for the same purpose (Sykes andGaunt 1976, Gaunt andBrak 1985).…”
Section: Introductionmentioning
confidence: 99%
“…d = 2 or 3. Previous work (Marro and Toral 1983) suggested that Binder's theory can provide a correct description of clusters in the three-dimensional Ising model outside the percolation region. Recent work by Cambier and Nauenberg (1986) also seemed to confirm these results in three dimensions but with different values for the critical exponents; their results for d = 2 were interpreted as showing a complete failure of the microscopic (Bruce and Wallace) model, but this was in contradiction with other computer simulations (Jan et a1 1982) and results obtained from the series expansions (Gaunt and Brak 1985).…”
Section: Introductionmentioning
confidence: 99%